Wirtualny podmiot Bukatmana - wprowadzenie - Mazurek, Marcin (Er(r)go. Teoria - Literatura - Kultura, 2002)
Marcin Mazurek, Bukatman’s Virtual Subject – Introduction The essays the concept of terminal identity as introduced by Scott Bukatman.